A 33-year-old patient with human immunodeficiency virus on antiretroviral therapy with efavirenz-induced complex partial seizures: a case report. (December 2016) - Shehu, Nathan; Ojeh, Victor; Osaigbovo, Godwin; Agaba, Patricia; Agbaji, Oche
Abstract Background Efavirenz is a commonly prescribed antiretroviral drug that is largely well tolerated. However, seizure disorder is a rare side effect. Prompt identification and immediate replacement of efavirenz with an alternative drug would effectively stop the seizures. To the best of our knowledge, we present the first reported case in the literature of complex partial seizures arising due to efavirenz. Case presentation We report a case of a 33-year-old Nigerian man treated with an efavirenz-based antiretroviral regimen for human immunodeficiency virus infection. He presented with seizures soon after commencement of antiretroviral drugs. His magnetic resonance imaging results were unremarkable. His blood levels of sodium, glucose, urea, and creatinine were within normal limits. However, his electroencephalogram showed intermittent bursts of high-voltage sharp waves and spikes bilaterally over frontotemporoparietal regions, a finding consistent with complex partial seizures. His efavirenz plasma level was 209.55 μg/ml. His seizures stopped following a switch to a non-efavirenz-based regimen. Conclusions This report brings to light the occurrence of complex partial seizures in patients on efavirenz. It also demonstrates the effective resolution of seizures when efavirenz treatment is replaced with a non-efavirenz-based regimen.